The nexus of poetics and psychotherapy: a neurobiological and substrative comparative analysis - Perkins, Selby Anne; Plisco, Mary (Journal of poetry therapy, 2025)
This paper contributes to the existing research literature by exploring neurobiological and theoretical overlaps between poetry and psychotherapy. Both poetry and therapy facilitate physiological changes in the brain that promote the development of emotional congruence, behavioral regulation, and salience integration. The similarity of effect is, in part, explained by the ways both therapy and poetry guide exploration through the freedom provided by their structures. The intentional participation required by both forms is also of import to the similarity of effect.